2011
DOI: 10.1007/s11095-011-0455-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Skin Permeability Relationship of Dendrimers

Abstract: The study demonstrates that the physicochemical properties of dendrimers influence their skin transport. Findings can be used to design dendrimer-based nanocarriers for drug delivery to skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 49 publications
6
56
0
Order By: Relevance
“…This implied that peptide dendrimers have the potential to swiftly deliver conjugated/complexed drug payloads when iontophoresis is applied. Our findings of passive diffusion and iontophoresis are consistent with previous results, where surface confocal images and hematoxylin-stained skin cryosections showed that the PAMAM dendrimer (G4-NH 2 ) was mostly distributed in stratum corneum upon passive diffusion; but in presence of iontophoresis, the dendrimer was found in viable epidermis with some permeation detected in the upper dermis layer [7]. …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This implied that peptide dendrimers have the potential to swiftly deliver conjugated/complexed drug payloads when iontophoresis is applied. Our findings of passive diffusion and iontophoresis are consistent with previous results, where surface confocal images and hematoxylin-stained skin cryosections showed that the PAMAM dendrimer (G4-NH 2 ) was mostly distributed in stratum corneum upon passive diffusion; but in presence of iontophoresis, the dendrimer was found in viable epidermis with some permeation detected in the upper dermis layer [7]. …”
Section: Resultssupporting
confidence: 92%
“…Accordingly, the flux values decreased significantly (p < 0.05) with an increase in molecular weight of dendrimers (≈ two-fold increase from 4 + to 8 + dendrimer and 8 + to 16 + dendrimer) although the positive charge density doubled from 4 + to 8 + dendrimer and then 8 + to 16 + dendrimer. These results are in accordance with a previous report in which the extent of skin permeation of PAMAM dendrimers decreased with increasing molecular weight [7]. The isoelectric point of the skin also cannot be ruled out for the enhanced iontophoretic transdermal permeation of peptide dendrimers.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In another study, Filipowicz et al (2011) also reported that the small-sized G2-NH 2 dendrimer might be a more potent penetration enhancer than the larger ones for the transdermal absorption of the hydrophilic drug (riboflavin) from the emulsions or hydrogels. Additionally, use of iontophoresis could further increase the skin penetration of cationic and neutral dendrimers into viable epidermis, which provided an effective method to delivery macromolecules into and across the skin (Venuganti et al, 2011).…”
Section: Dendrimersmentioning
confidence: 99%